Remote sensing in geoscience - Tripathi, Nitin Kumar; Bajpai, Vishwa Nath.; Gokhale, K. V. G. K. (New Delhi : Anmol Publications, 1998)
Contributed articles presented on the sixtieth birthday of Prof. K.V.G.K. Gokhale; with special reference to India.
Includes bibliographical references.
Amirul
Keywords: Earth sciences -- India -- Remote sensing; Geology -- India -- Remote sensing